2011
DOI: 10.1105/tpc.111.085464
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Analysis of aMedicago truncatula smooth leaf margin1Mutant Reveals Context-Dependent Effects on Compound Leaf Development  

Abstract: Compound leaf development requires highly regulated cell proliferation, differentiation, and expansion patterns. We identified loss-of-function alleles at the SMOOTH LEAF MARGIN1 (SLM1) locus in Medicago truncatula, a model legume species with trifoliate adult leaves. SLM1 encodes an auxin efflux carrier protein and is the ortholog of Arabidopsis thaliana PIN-FORMED1 (PIN1). Auxin distribution is impaired in the slm1 mutant, resulting in pleiotropic phenotypes in different organs. The most striking change in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 83 publications
(169 reference statements)
4
119
0
Order By: Relevance
“…Interestingly, in M. truncatula, leaves of the MtPIN10/SLM1 (the Medicago PIN1 ortholog) mutant exhibit increased complexity and decreased marginal patterning, suggesting a more complex effect of auxin on leaf patterning in Medicago. However, the increased complexity might result from fusion of several leaves (Peng and Chen, 2011;Zhou et al, 2011).…”
Section: Marginal Patterning In Simple and Compound Leavesmentioning
confidence: 99%
“…Interestingly, in M. truncatula, leaves of the MtPIN10/SLM1 (the Medicago PIN1 ortholog) mutant exhibit increased complexity and decreased marginal patterning, suggesting a more complex effect of auxin on leaf patterning in Medicago. However, the increased complexity might result from fusion of several leaves (Peng and Chen, 2011;Zhou et al, 2011).…”
Section: Marginal Patterning In Simple and Compound Leavesmentioning
confidence: 99%
“…To investigate the location of auxin signaling during infection, we used M. truncatula stably transformed with the auxin reporter DR5:GUS (Zhou et al, 2011) and observed that S. meliloti induced DR5:GUS in both infected and uninfected root hairs over the entire infection zone (root hair differentiation zone) 3 and 5 dpi ( Figures 7A and 7B). This increase in auxin signaling is consistent with the observation that auxin signaling is initially downregulated and then increases at the site of inoculation (Mathesius et al, 1998).…”
Section: Auxin Signalingmentioning
confidence: 99%
“…The primers used are listed in Supplemental Table 1 (Primers). The DR5:GUS analysis was performed in the R108 background using a stably transformed line (Zhou et al, 2011;Guan et al, 2013).…”
Section: Promoter-gus Analysismentioning
confidence: 99%
“…The formation of marginal serration tips is tightly correlated with auxin activity maxima, and the formation of lateral veins is defined by internalizing auxin through the center of the serrations. Perturbation of auxin transport by 1-N-naphthylphthalamic acid results in smooth leaf margins (DeMason and Chawla, 2004;Hay et al, 2006;Barkoulas et al, 2008;Zhou et al, 2011a). The second process is the repression of growth at the sinus by CUP-SHAPED COTYLEDON2 (CUC2).…”
Section: Introductionmentioning
confidence: 99%
“…In the model legume Medicago truncatula, the orthologs of Arabidopsis PIN1 and CUC have been identified and named SMOOTH LEAF MARGIN1 (SLM1) and NO APICAL MERISTEM (NAM), respectively (Zhou et al, 2011a;Cheng et al, 2012). The slm1 mutant exhibits a smooth leaf margin as a result of diffuse auxin distribution, suggesting the conserved roles of the auxin/SLM1 module in different plant species (DeMason and Chawla, 2004;Barkoulas et al, 2008;Koenig et al, 2009;Zhou et al, 2011a). In addition, the loss of function of SLM1 or NAM in M. truncatula leads to defects in the separation of lateral organs, indicating that both of them are positively correlated with the promotion of organ boundaries.…”
Section: Introductionmentioning
confidence: 99%